A Comparison of Motives and Entry Strategy between State-owned Chinese Firms and Private Chinese Firms - LI, FANGZHOU (2014)
With the current growth from emerging economies multinational enterprises, more attention is being directed to their motives and entry strategies. In this essay, Chinese multinational corporations (MNCs) are chosen as the representative of emerging economies MNCs. However, there are various kinds of Chinese MNCs that cannot fit neatly into one single group. Hereby, Chinese MNCs are classified as privately-owned enterprises (POEs) and State-owned enterprises (SOEs). POEs and SOEs are analysed and compared in terms of their motives and entry strategies. Case study, in which the research method is employed, is used to analyse it. Although the research result has been criticized for its generalizability, the scarcity of theories on emerging economies outward FDI renders case study an explanatory, descriptive and explorative approach to deriving deep insights from the case. CNOOC and Huawei are chosen as SOEs and POEs respectively to specify the difference in terms of motives and entry strategies. In the final analysis, POEs are more likely to be driven by economic rationality while SOEs by government intentions. Backed up by the government, SOEs are more likely to take a “leap frog” step which commits more resources. But POEs are likely to take incremental approach towards internationalization. The main objective is to improve the understanding of Chinese outward FDI by comparing SOEs and POEs’ entry strategies as well as motives to provide possible directions for future research.